Court touts tarnish justice system - Malay, Mail (Malay Mail, 2015)
Kuala Lumpur- Touting activity has been detected at the Kuala Lumpur Court Complex, involving unscrupulous people who act as intermediaries between lawyers and the courts to settle cases with the payment of a certain amount.